Correlation of a mobile‐based cognitive test app with traditional neuropsychological tests in a community‐based cohort. (31st December 2021) - Au, Rhoda; Devine, Sherral; Young, Katie; McManus, Chelsea; Lin, Honghuang
Abstract: Background: Over the past decade, a number of digital health devices and mobile apps have been developed to monitor cognitive health. These digital technologies provide the potential as a convenient and cost‐effective solution for cognitive health. However, many of them were tested only in a controlled environment with limited samples, whereas their validity for longitudinal cognitive health monitoring is largely unknown. Method: The study included participants from the Framingham Heart Study (FHS) who previously completed traditional neuropsychological (NP) tests in the FHS research center. Participants were asked to complete additional cognitive tests using Defense Automated Neurobehavioral Assessment (DANA), which is the first FDA cleared mobile app with 9 different cognitive tests, including Code Substitution, Go No Go, Insomnia Severity Index, Match to Sample, Memory Search, Patient Health Questionnaire, Procedural Reaction Time, Simple Reaction Time, and Spatial Processing. Participants were asked to complete at least three tests at the baseline, and every three months. The correlation between DANA tests and 18 traditional NP tests were assessed by the Pearson correlation coefficient test. Result: One hundred and twenty one participants were included in the current study (mean age 71±8, 64.5% women). These participants completed an average of 2.9 repetitive tests during a median of seven month follow‐up period. All DANA tests were correlated with at least one NP test with nominal significance ( P <0.05). Three NP tests were correlated with Procedural Reaction Time and two NP tests were correlated with Code Substitution after Bonferroni correction for multiple testing ( P <3.1x10 ‐4 ). The most significant correlation was observed between Procedural Reaction Time from DANA and the Trails B test that was conducted in the FHS research center, with correlation coefficient of 0.44 ( P =6.8x10 ‐7 ). The correlation remained significant during follow‐up DANA tests (correlation coefficient=0.44, 0.34, and 0.41 for the 2 nd, 3 rd and 4 th DANA exams, respectively). Conclusion: Our study suggests that traditional NP tests were highly correlated with some DANA tests, which might be used as an alternative approach for habitual cognitive health monitoring in a person's natural environment.